2006
DOI: 10.1007/s10753-006-9002-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish or Soybean Oil-Rich Diets on Bradykinin, Kallikrein, Nitric Oxide, Leptin, Corticosterone and Macrophages in Carrageenan Stimulated Rats

Abstract: We have previously demonstrated that both n-3 and n-6 polyunsaturated fatty acids (PUFA)-rich diets decrease the acute inflammatory response partially explained by the high corticosterone basal levels. The present study aimed to determine the effect of hyperlipidic diets (PUFA n-3 or n-6) on phagocytosis, hydrogen peroxide (H(2)O(2)) and nitric oxide (NO) release by macrophages, bradykinin (BK) and NO release in the paw inflammatory perfusate and Kallikrein (KK), corticosterone and leptin blood levels. Hyperli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
4
8
0
Order By: Relevance
“…However, the daily energy intake was lower in S and F as compared to C (Table 3). These findings are in accordance with previous data [13,17,42]. The C, L, and CC mice had similar energy intakes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the daily energy intake was lower in S and F as compared to C (Table 3). These findings are in accordance with previous data [13,17,42]. The C, L, and CC mice had similar energy intakes.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that treatment for 7 weeks with the same soybean oil-enriched diet used in this study increased plasma corticosterone concentrations [42]. The reduced adiponectin gene expression observed in the chronically treated S group may be attributed, at least in part, to an increase in glucocorticoid levels, which, according to Fasshauer et al [11], decrease adiponectin gene expression.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Nutrition therapy in critically ill patients may play an important role in assisting recovery and improving outcomes 5 , 6 . The capacity of ω‐3 polyunsaturated fatty acids (PUFAs) to modulate immunologic and inflammatory responses has been recognized for some years 7 10 . The biologically active ω‐3 PUFAs are eicosapentaenoic acid (EPA; 20:5ω‐3) and docosahexaenoic acid (DHA; 22:6ω‐3) found in fish oils.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) It is therefore conceivable that soybean oil has low toxicity in the lungs because these components inhibit the toxicity of OA.…”
Section: Discussionmentioning
confidence: 99%